2017
DOI: 10.15171/ajmb.2017.09
|View full text |Cite
|
Sign up to set email alerts
|

Molecular studies on preproghrelin gene: Signal peptide, ghrelin coding region and variants – A brief report focusing on rs34911341 polymorphism

Abstract: Background: Ghrelin is a hormone that exhibits effects in a lot of biologic processes, such as food intake regulation, gastrointestinal motility and carbohydrate metabolism. Ghrelin is encoded by human preproghrelin gene (GHRL), reported with four exons. However, experiments suggested a new molecular structure for this gene. Objective: This study aims to clarify by a simple representation GHRL and its products, showing the variants described for this gene up to this moment. Methods: The GHRL sequence for mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In conclusion, the ghrelin gene variation R51Q was previously investigated clinically, and it was found to be associated with metabolic syndrome, 13,30 hypertension, 31 obesity, 32 and gastric cancer. 33 In the current study, it was revealed that this mutation did not result in observable conformational changes in the C-terminal of the ghrelin model hormone, but it did affect the final stability of the complex by generating new molecular interactions between the ligand and receptor models followed by decreased its total energy.…”
Section: Models Preparations and Molecular Dockingmentioning
confidence: 88%
See 1 more Smart Citation
“…In conclusion, the ghrelin gene variation R51Q was previously investigated clinically, and it was found to be associated with metabolic syndrome, 13,30 hypertension, 31 obesity, 32 and gastric cancer. 33 In the current study, it was revealed that this mutation did not result in observable conformational changes in the C-terminal of the ghrelin model hormone, but it did affect the final stability of the complex by generating new molecular interactions between the ligand and receptor models followed by decreased its total energy.…”
Section: Models Preparations and Molecular Dockingmentioning
confidence: 88%
“…The arginine residue at position 28 of the mature ghrelin hormone was thought to be essential for endoprotease identification and action. 13 Endoprotease catalyzes the proteolytic cleavage during the production of ghrelin. 14,15 Yet, it is unclear if this genetic variation alters ghrelin's physiologic characteristics or action.Ghrelin and ghrelin receptor agonists can effectively treat anorexia and cachexia in cancer 16,17 and chronic kidney disease patients.…”
mentioning
confidence: 99%